A Study on Tribal Development Programme, Schemes & Policies for Tribal in Rajasthan: Exploring Tribal Development and Policies in Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The Programme on Integrated Tribal Development Projects (ITDP) under Tribal Sub-Plan (TSP) isbeing implemented since the Fifth Five Year Plan with specific objectives of reducing poverty, improvingeducational status an eliminating exploitation of the tribal families. The schemes of the Ministry of TribalAffairs are demand driven and funding are made in various sectors including for employment-cum-incomegeneration and covers activities such as establishment of AgroForestNatural Resource based micro village industries through training of tribal cooperatives, SHGs and individual entrepreneurs, promotionand skill development in traditional tribal culture areas like tribal jewellery, painting, dance forms, musicand culinary art, Village tourism, Eco-tourism, etc. The wellspring of power among the majority has beencredited to such awareness. India is a place that is known for different regulations on an assortment ofsubjects. The vast majority of these relate to the advantages of individuals. But due to the lack of theirawareness for such provisions hardly yield any benefit to them. In the different Census Reports andinvestigations of the Castes and Tribes, they have been called by different names, similar to 'nativeclans', 'crude clans', 'tribal populaces', 'animists', 'Hindu tribals', and so on .Scheduled Tribes are those,which are advised as such by the President of India under Article 342 of the Constitution.